Function of juvenile plumage in the northern goshawk (Accipiter gentilis): aggressive mimicry hypothesis - Jan Špička; Petr Veselý; Roman Fuchs (Journal of Avian Biology, 2024)
Multiple raptors show juvenile plumage that is substantially different from that of their parents. Here, we test the prediction that the colouration of the juvenile northern goshawk Accipiter gentilis resembling the colouration of the common buzzard Buteo buteo acts as a form of aggressive mimicry. The goshawk specialises in hunting larger birds and mammals up to the size of geese or hares, while the buzzard preys mostly on small rodents. Larger birds may thus consider juvenile goshawks as less dangerous raptors, and the juvenile goshawk may thus gain an advantage when hunting. We used the Eurasian magpie Pica pica, a common prey of the goshawk, to test this prediction. We compared the behavioural responses of magpie parents defending their freshly fledged young towards mounts of an adult goshawk, juvenile goshawk, and buzzard. To be able to assess whether this behaviour differs from responses to a nest predator and a harmless bird we also presented a common raven Corvus corax and common pheasant Phasianus colchicus as baseline stimuli. Both juvenile and adult goshawks elicited antipredatory behaviour, but magpies took more risks facing juvenile goshawks. Additionally, the intensity of antipredatory behaviour towards the juvenile goshawk was also higher than towards the buzzard. We thus conclude that magpies do distinguish between juvenile and adult goshawks, as well as they do distinguish juvenile goshawks from buzzards. They are able to assess the threat particular raptors represent and respond accordingly. Analysis of spectral reflectance of stuffed specimens of these three raptors suggests there are differences, which can be used for the appropriate recognition. In conclusion, we cannot confirm the hypothesis of aggressive mimicry in juvenile goshawks that interact with magpies.